Pengaruh Corporate Governance Terhadap Firm Value Dengan Earning Quality Sebagai Variabel Intervening Pada Perusahaan Yang Terdaftar di LQ45 - Florensia Venna Clarista; Devie Deviesa (Business Accounting Review, 2017)
The purposes of this research is to analyze the relationship of corporate governance to firm value with earning quality as intervening variable. The data analysis technique used was Partial Least Square (PLS) with the calculation process assisted by SmartPLS software application program to process the data from the Annual report. The results showed there were positive and significant influence of corporate governance towards firm value, positive and siginificant influence of corporate governance towards earning quality, and earning quality towards firm value, but there was no indirect influence of corporate governance towards firm value through earning quality